<em>u={1,2,3,4,5},A={2,4} and Beta {2,5,5}</em>
<em>now</em><em>,</em><em> </em><em>(AUB)</em><em>=</em><em>{</em><em>1</em><em>,</em><em>3</em><em>,</em><em>3</em><em>,</em><em>4</em><em>,</em><em>5</em><em>}</em>
<em>[</em><em>AUB</em><em> </em><em>is</em><em> </em><em>the</em><em> </em><em>set</em><em> </em><em>of</em><em> </em><em>all</em><em> </em><em>elements</em><em> </em><em>of</em><em> </em><em>set</em><em> </em><em>A</em><em> </em><em>and</em><em> </em><em>set</em><em> </em><em>B</em><em> </em><em>without </em><em>any</em><em> </em><em>repetition </em><em>]</em>
<em>n</em><em>(</em><em>AUB</em><em>)</em><em>=</em><em>5</em>
<em>n</em><em>(</em><em>AUB</em><em>)</em><em>is</em><em> </em><em>the</em><em> </em><em>total</em><em> </em><em>no</em><em> </em><em>of</em><em> </em><em>elements</em><em> </em><em>in</em><em> </em><em>set</em><em> </em><em>(</em><em>AUB</em><em>)</em>
Answer:
5 and 6
Step-by-step explanation:
5 and 6
Answer:
The length of the other would be 36.
Step-by-step explanation:
a² + b² = c²
b² = c² - a²
b² = 60² - 48²
b² = 3600 - 2304
b² = 1296
√b² = √1296
b = 36
<span><span>the exact answer is 3 over
<span>5√</span> </span>35</span>